Engineering mechanics. Statics - Hibbeler, R. C. (Upper Saddle River, NJ : Prentice Hall, 2010)
Engineering Mechanics: Statics in SI Units, 12e provides students with a clear and thorough presentation of the theory and applications of this subject. By improving on the content, pedagogy, presentation and currency over the 12 editions, HibbelerEngineering Mechanics: Statics in SI Units, 12e provides students with a clear and thorough presentation of the theory and applications of this subject. By improving on the content, pedagogy, presentation and currency over the 12 editions, Hibbeler$1 (Bs Engineering Mechanics series is renowned for its clarity of explanation and robust problem sets; making it the best-selling course text for this subject.s
1. General Principles -- 2. Force Vectors -- 3. Equilibrium of a Particle -- 4. Force System Resultants -- 5. Equilibrium of a Rigid Body -- 6. Structural Analysis -- 7. Internal Forces -- 8. Friction -- 9. Center of Gravity and Centroid -- 10. Moments of Inertia -- 11. Virtual Work.
Includes index.
1
Keywords: Statics